Analisis Persepsi Harga Terhadap Keputusan Pembelian Sepeda Listrik Merek U-Winfly - Novi Rahmayanti; Melita Sugiarti; Syamsul Hadi (Ebisnis Manajemen, 2024)
In this modern era, business growth is occurring very rapidly. Various businesses are developing everywhere, the number of prices and quality of products is becoming more diverse, making market competition fierce. The growth of technology can also have a big influence on human life, one of which is growth in the field of vehicles such as electric bicycles. Electric bicycles are bicycles powered by electricity and electric bicycles are transportation that does not cause air pollution. The aim of this research is to reduce air pollution and utilize advanced technology, so electric bicycles are needed. This research used a quantitative method with 348 employee class students majoring in law at Bina Bangsa University and the collection method used the Slovin formula. The data analysis used in this research is multiple linear regression analysis and the results are significant. Shows that price perception influences interest in purchase intention U-Winfly brand electric bicycles.